A compact, modular, multi-wavelength (200–850nm) rotating-analyzer ellipsometer for optical constant characterization of nanostructured materials. (2nd October 2020) - Agus Putra Dana, I Ketut; Jatmiko, Puthut Dwi; Suharyadi, Edi; Santoso, Iman
Abstract: We have developed a compact modular rotating-analyzer ellipsometer (RAE) with a spectrum range of 200–850 nm. Spectroscopic ellipsometry is a non-destructive characterization based on an optical method. It is used widely to obtain the dielectric constant, thickness, and surface roughness of thin films. Our homemade RAE comprises standard modular components that are available on the market, such as (i) a deuterium–halogen DH-2000-BAL light source made by Ocean Optics, (ii) a Rochon prism with an α -BBO substrate from Edmund optics for the polarizer and analyzer, and (iii) a Red Tide USB650UV mini detector from Ocean Optics and a compact ellipsometer arm design to ensure its ease-of-use and future development. Data acquisition is automated and can be controlled using a computer program, and all the moving parts are motorized. The dielectric constant of Au film with a thickness of 300 nm has been measured for calibration of the apparatus. The result was compared with reference measurements that used a commercial ellipsometer, and showed considerable accuracy with a similarity of ∼95%.